The Perception and Attitude of Residential Care Elders at the House of Elders in Tirana towards Residential Services and the Approach of Integrated Social Services - Brunilda Dervishaj Hoxhaj (European Scientific Journal, ESJ, 2016)
This study is a quantitative study which is aimed at showing the perception and atittude of residential elders at the House of Elders in Tirana. For three different days, I obtained questionnaires from all elders of these institutions. At the start of this study, I analysed the available literature as a method of data collection, from which I got the topic of this analysis. From the collection of the basic data of this study, I created and used a 10 question questionnaire. The method of census was choosen as the method of deciding the measurements, because of my intention of studying all the elders of the House of Elders in Tirana. The excel program was used for working through the statistics. After analysing the quantitative data, there were three conclusions. Firstly, males and females prefer more integrated social services than residential services. Secondly, even though the elders feel protected and safe at the House of Elders in Tirana, they mostly expressed that they missed the family environment. They emphasized that if the System of Social Defence offered them home social services, a high number of elders will not remain at the House of Elders. However, this study can be used by policy makers of the elders services and institutions from which we obtained the data for this study to improve their services as well as offer services in the home-family way.